A presença de processos autogestionários nos empreendimentos de economia solidária pesquisados pelo SIES e a contribuição do campo CTS - Tucci, Celso Geraldo (2012)
Frequent crises characterized capitalism, which are manipulated by him to concentrate more wealth and increase control over the working class, with the permanent threat of unemployment. Even more, it creates a world of consumerism that creates alienation, because work is needed to consume and to continue to have work you need to accept the capitalist rules. The objective of this research is to identify as the National Information System on the Solidarity Economy - SIES, to provide data about economic and supportive projects, obtained through field research, establishes itself as a social technology that contributes to the processes of self-management features of the Solidarity Economy. As preparatory steps for the analysis of data provided by SIES, the study follows a path that seeks to set the historical focus: its economic structure dominant, neoliberal capitalism and globalization, the new concept of territorial development that guides the Solidarity Economy, which if you want to organizing democratic and egalitarian forms of production, consumption, savings and loans as an alternative to the dominant system, and finally, a new line of thought represented by the studies STS (Science, Technology and Society), with a new vision of relations between scientific and technological progress and its impact on the dynamics of development of society. Questions of Solidarity Economy are discussed in detail in a separate chapter, as well as the process of self-managed firms, constitute the essence of solidarity enterprises. To reach that goal, we used the exploratory method, starting from the case studies of projects offered by SIES solidarity, which give an updated scenario of the Solidarity Economy in the five Brazilian regions, from the perspective of the field Science, Technology and Society - STS . The conclusions of the study point to the fact that multidisciplinary interventions contribute to the construction of an alternative to the capitalist mode of production, for which the field STS could contribute. Also point to significant growth, and also qualitatively, the Solidarity Economy movement, possibly from the successive crises of capitalism and also a change of understanding of the ways economic organizations may be beyond the capitalist structures, just as demonstrates the relationship of projects with various social movements, even though, according to data from SIES, the initiatives are still shy when it comes to more specific interventions in the territory surrounding the developments.